A simple device for the calibration of the Optical Wedge of the Dobson's Ozone Spectrophotometer - SINHA, S. S.; SANYAL, S. K. (MAUSAM, 1965)
The calibration of the optical wedge of the Dobson's Ozone Spectrophotometer is being done by the two well known methods, viz., (1) from sunlight with the help of perforated gauze and (2). by rhodiumised plate and standard lamp, the transmission coefficients of perforated gauze and rhodiumised plate being known. In this paper the result of the calibration of the optical wedge of the Dobson's Spectrophotometer by means of a circular diaphragm cutting the light intensity from a standard lamp to a known percentage has been explained.